Analysis of Student Behavior Towards Positive Discipline Culture of Obeying School Rules at UPTD SDN Banyuajuh 6 - Putri, Arda Febrianti Ananda Eka; Setyawan, Agung (Citra Dharma Cindekia, 2024)
The purpose of this study is to describe the application of positive discipline culture behavior to obey school regulations carried out at UPTD SDN Banyuajuh 6. This study uses a descriptive quantitative method. The population of this study is all students at UPTD SDN Banyuajuh 6 with a total of 117 students. The research sample was 20% or as many as 23 students with the Purposive Sampling technique. The research data was collected using questionnaire instruments such as statements of student compliance with school rules, interviews, and observation sheets on the implementation of school discipline regulations. The data analysis technique used is an instrument validity test with the Aiken V formula to calculate the results of instrument validation by experts. The results showed that out of 23 students, only 56.23% or 13 students had applied the criteria for cultivating. Then 43.47% or 10 students who applied the criteria began to develop. This means that there is an application of student behavior towards positive discipline to obey school regulations at UPTD SDN Banyuajuh 6. The implementation of positive discipline culture in this study has been implemented and shows the criteria for cultural culture quite well.